Metaheuristic Algorithms Enhanced Multi-Modal Sensor Fusion for Object Recognition in Autonomous Vehicles - Ghosh, Debom (My University, 2025)
This research details a sensor fusion framework for autonomous vehicles. Our hy- brid architecture brings together two datasets— KITTI and BDD100k—to serve a singular purpose. That is, our primary contribution is the development of an adap- tive feature selection mechanism that dynamically tunes to different sensor fusion algorithms. The real-time tuning of the tunable parameters results in an optimiza- tion of the data being fused from the vehicle’s heterogeneous, multi-modal sensor suite—specifically, from a 64-channel (or 32-channel) LiDAR and an array of multi- spectral cameras. The architecture proposed here introduces three key innovations. First is the hier- archical feature extraction pipeline, which uses spatio-temporal correlations across modalities to perform feature extraction in a computationally efficient way and to a high degree of accuracy. Second is the adaptive weight optimization strategy, which uses different sensor modalities to make the necessary changes to the weights of the features extracted from the different environmental sensors. The third innovation is an optimization framework that works in real-time and maintains a high degree of visual fidelity while also being robust enough to perform well across many dif- ferent kinds of scenes. The overall architecture is thoroughly validated on several industry-standard datasets (i.e., BDD and KITTI), and the methods used therein are evaluated over several ablation studies to verify the necessity and sufficiency of all the components of the architecture. The framework’s reliability across different operational situations is confirmed by thorough validation through 10-fold cross-validation and statistical significance test- ing (p < 0.01). It appears to work particularly well in trying conditions—like signif- icant rain or fog, or nighttime—where old-fashioned, single-sensor approaches often perform poorly.
Keywords: multi-sensor fusion, feature extraction, feature optimization, sensor fusion, object detection, intelligent driving assistance, autonomous vehicles